Samoglasniki v stiku - Skubic, Darija (Jezik in slovstvo, 2018)
The topic of our research is the phonetic interferences and characteristics of the pronunciation of vowels by Slovenian-Italian bilingual speakers from Trieste and by monolingual Slovenians from Slovenia. By analysing Slovenian vowels (formants) we tried to identify the differences in the vowel space of monolingual and bilingual Slovenian speakers and to determine whether bilingual speakers have one or two vowel systems. The results show that the Italian language and the Trieste dialect exert a strong influence on the vocalic system of bilingual speakers, as the formants of their Slovenian vowels (at F1 or/and F2) differ significantly in variability and average value from those of monolinguals. All of the formants, except for F1 and F2 of stressed and unstressed /a/ and /%/, differ significantly between the two groups. It can be concluded that Slovenian speakers from Trieste have an independent and unitary vowel system.
Keywords: bilingvizem; formanti; govorci; italijanščina; samoglasniki; slovenščina; sociofonetika; Trst